A review on different treatment methods for enhancing the properties of recycled aggregates for sustainable construction materials - Mistri, Abhijit; Bhattacharyya, S.K.; Dhami, Navdeep; Mukherjee, Abhijit; Barai, S.V. (ELSEVIER SCI LTD, 2020)
With global increase in construction and demolition, recycling of construction debris as an aggregate can be a vital step towards achieving sustainability in concrete construction. However, a clear methodology for reuse of construction and demolition (C&D) waste in concrete is warranted for its use in practice. This paper reviews the challenges revealed hitherto such as weak interfacial transition zone, high water absorption and presence of micro cracks in the use of C&D wastes as the recycled aggregate (RA). Methods of mitigation of these weaknesses through various treatments have been reported. This review has a special focus on India, a country that generates one of the world's highest quantity of C&D waste. After analysing all the treatment methods, the authors summarize that the strengthening of attached mortar (AM) technique is better than removing of AM, which is also cost-effective, eco-friendly and sustainable. Use of nano-materials and pozzolana along with different mixing methods and application of bio-cement is found to be superior and environmental friendly approach for improving the properties of recycled aggregates.